Astaxanthin Protects OTA-Induced Lung Injury in Mice through the Nrf2/NF-κB Pathway - Xu, Weixiang (Toxins (Basel), 2019)
The aim of this research was to evaluate the potential protective mechanism of astaxanthin (ASTA) against oxidative damage and inflammation caused by ochratoxin (OTA) in mouse lung. We divided mice into a control group (CG), an OTA group (PG), an astaxanthin group (AG), and an OTA+ASTA group (JG). Oxidative indices (malondialdehyde (MDA), total superoxide dismutase (T-SOD), and reduced glutathione (GSH)) and inflammatory markers (interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α)) were assayed in the lung, and the lung-weight-to-body-weight ratio was calculated. Apoptosis was detected in pathological sections by the TdT-mediated dUTP nick-end labeling (TUNEL) assay. Oxidative damage and inflammation were detected in the lung of mice after exposure to OTA. Besides, Nrf2- and NF-κB-pathway-associated proteins were detected by Western blot. In contrast with OTA, ASTA significantly raised the expression of Nrf2, HO-1, and MnSOD, while the expression of other proteins (Keap1, TLR4, and NF-κB) was significantly decreased. These results indicate that ASTA exerted protective effects against OTA-induced oxidative damage and inflammation in the lung by regulating the Nrf2 and NF-κB pathways.